Postpandemic Influenza A/H1N1pdm09 is still Causing Severe Perinatal Complications - Bogers, Hein (Mediterr J Hematol Infect Dis, 2015)
Although influenza A/H1N1pdm09 is not causing a pandemic anymore, we recently observed two critically ill pregnant women infected by this virus. We present these cases to illustrate the possible severe complications of an – at that moment – seasonal influenza in pregnancy. We discuss the epidemiological differences between the pandemic and post pandemic phase and try to explain the high virulence of influenza A/H1N1pdm09 -infections in pregnancy by discussing insights in immunology during pregnancy. We conclude that although influenza A/H1N1pdm09 is in the post pandemic phase, infection by this influenza virus still needs to be considered in pregnant women with progressive respiratory dysfunction.